(3GdJUQjM aj TQM GdJSQjMs - (3Ydj Hf (B((3SdWGf(B) (3eMeO, fhQ GdOjf GdedG GdgQhj GdbGQj,J (B1014 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Rjf GdYHGO HeG CQGO CeG HYO ai GdehWC Yf RjO Hf CSde Yf YWGA Hf jSGQ Cf QShd Gddg Udi Gddg Ydjg hSde (B" (3QCi QLdkG KGFQ GdQCS hGddMjI aCTGQ Edjg HEUdGM QCSg hdMjJg (B" s
(3BNQgG (B:s
(3hSFd CHh jRjO gd dMjJc CaVd Ce PfH GdcdH abGd Ef eJ Ydi GdESdGe adMjJi CaVd hEdG aPfH GdcdH Cced s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B17s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B12 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B100s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B136) s
Keywords: (3GdeLGejYs